Freedom of Speech as a Pillar of Equality in Indonesia in The Context of Constitutional Law - Yovan Iristian (PT. Banjarese Pacific Indonesia, 2024)
The important role of freedom of expression as a basis for equality, especially within the framework of constitutional law, is very important in Indonesia. This research uses normative juridical qualitative methods to obtain a comprehensive understanding of the legal aspects that regulate freedom of expression in the country. Recognized as an essential human right, freedom of expression is explicitly protected by the 1945 Constitution of the Republic of Indonesia. The focus of this research is to examine the legal norms governing freedom of expression, which include provisions such as Article 28E paragraph (3) and Article 19 of the Constitution 1945, as well as other statutory regulations. The research results show that freedom of expression is recognized as an inalienable right by the state and is one of the foundations for the realization of a just and democratic society. Although freedom of expression is guaranteed by the constitution, this research also highlights the obstacles and challenges in its implementation. In Indonesia, challenges arise in navigating diverse interpretations of freedom of expression, with concerns about potential exploitation by entities harming public interest. Striking a balance between freedom of expression and societal stability/security is deemed crucial. The research aims to better understand the complexity of freedom of expression within the country's constitutional law and its role in promoting equality. This research aims to find useful insights for creating better policies. These policies should strike a good balance between individual freedom and public interest, ultimately fostering a fair and democratic society.